Measurement of CP-Averaged observables in the B0→K*0(→K+π−)μ+μ− decay - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2020)
An angular analysis of the B0→K*0(→K+π−)μ+μ− decay is presented using a dataset corresponding to an integrated luminosity of 4.7 fb−1 of pp collision data collected with the LHCb experiment. The full set of CP-averaged observables are determined in bins of the invariant mass squared of the dimuon system. Contamination from decays with the K+π− system in an S-wave configuration is taken into account. The tension seen between the previous LHCb results and the standard model predictions persists with the new data. The precise value of the significance of this tension depends on the choice of theory nuisance parameters.
LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, M. Dziewiecki, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, H. Malygina, J. Marks, S. Neubert, A. Piucci, N. Skidmore, S. Stemmle, U. Uwer, L. Witola, A. Zhelezov [und viele weitere]
Im Titel steht B(Null, hochgestellt) ->K*(Null, hochgestellt)griech. m+griech.m- decay
Gesehen am 14.09.2020